Optimization of initial propofol bolus dose for EEG Narcotrend Index‐guided transition from sevoflurane induction to intravenous anesthesia in children. Issue 4 (18th February 2017) - Dennhardt, Nils; Boethig, Dietmar; Beck, Christiane; Heiderich, Sebastian; Boehne, Martin; Leffler, Andreas; Schultz, Barbara; Sümpelmann, Robert
Summary: Background: Sevoflurane induction followed by intravenous anesthesia is a widely used technique to combine the benefits of an easier and less traumatic venipuncture after sevoflurane inhalation with a recovery with less agitation, nausea, and vomiting after total intravenous anesthesia (TIVA). Combination of two different anesthetics may lead to unwanted burst suppression in the electroencephalogram (EEG) during the transition phase. Objective: The objective of this prospective clinical observational study was to identify the optimal initial propofol bolus dose for a smooth transition from sevoflurane induction to TIVA using the EEG Narcotrend Index (NI). Methods: Fifty children aged 1–8 years scheduled for elective pediatric surgery were studied. After sevoflurane induction and establishing of an intravenous access, a propofol bolus dose range 0–5 mg·kg −1 was administered at the attending anesthetist's discretion to maintain a NI between 20 and 64, and sevoflurane was stopped. Anesthesia was continued as TIVA with a propofol infusion dose of 15 mg·kg −1 ·h −1 for the first 15 min, followed by stepwise reduction according to McFarlan's pediatric infusion regime, and remifentanil 0.25 μg·kg −1 ·min −1 . Endtidal concentration of sevoflurane, NI, and hemodynamic data were recorded during the whole study period using a standardized case report form. Propofol plasma concentrations were calculated using the paedfusor dataset and a TIVA simulation program. Results: Median endtidal concentration of sevoflurane at the time of administration of the propofol bolus was 5.1 [IQR 4.7–5.9] Vol%. The median propofol bolus dose was 1.2 [IQR 0.9–2.5] mg·kg −1 and median NI thereafter was 33 [IQR 23–40]. Nine children presented with a NI 13–20 and three children with burst suppression in the EEG (NI 0–12); all of them received an initial propofol bolus dose >2 mg·kg −1 . Regression equation demonstrated that NI 20–64 was achieved with a 95% probability when using a propofol bolus dose of 1 mg·kg −1 after sevoflurane induction. Decrease in mean arterial blood pressure correlated significantly with propofol bolus dose ( P = 0.038). After 25 min of TIVA, children younger than 2 years had a higher NI (median difference 14.0, 95%CI: 6.0–20.0, P = 0.001), higher deviations from the expected Narcotend Index (median difference 4.1, 95%CI: 3.9–4.2, P < 0.001) and lower calculated propofol plasma concentrations (median difference 0.2 μg·ml −1, 95% CI: 0.1–0.3 μg·ml −1, P < 0.001) than older children. Conclusion: After sevoflurane induction, a reduced propofol bolus dose of 1 mg·kg −1 followed by TIVA according to McFarlan's regime resulted in a NI within the recommended range in children aged 1–8 years. During the course of TIVA, children younger than 2 years displayed higher NI values and more pronounced interindividual variation. Processed EEG monitoring is recommended to find adequate individual age‐dependent doses. Abstract :